Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kepuasan Kerja: Studi Pada Salah Satu Instansi Pemerintah di Kabupaten Bandung - Ruddy Heryadi; Soelaiman Sukmalana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
This research departs from phenomena that indicate inadequate job satisfaction caused by low work motivation and employee discipline. For this reason, the research aims to analyze the effect of work motivation and work discipline on job satisfaction. Quantitative research method approach using employee respondents who work in one of the government agencies in Bandung Regency as many as 120 employees. The sample frame uses the rank and work class of employees. The data analysis technique uses path analysis with results showing an influence of work motivation and work discipline on employee job satisfaction. The actual influence is 58.2%, while the rest influence by other factors not examined in this study.